PENGARUH PROFITABILITAS, ASSET INTENSITY, EMPLOYEE INTENSITY, FREE CASH FLOW, LEVERAGE, DAN SIZE TERHADAP COST STICKINESS DENGAN TOBIN’S Q SEBAGAI VARIABEL KONTROL (Studi Kasus Perusahaan Manufaktur di Bursa Efek Indonesia Tahun 2016-2020) - Taurisia Dinda Herfanti; Prasetiono Prasetiono (Diponegoro Journal of Management, 2023)
ABSTRACT This research examined the effect of profitability, asset intensity, employee intensity, free cash flow, leverage, and size on cost stickiness with tobin’s q as control variable. Cost stickiness was measured using the changes in selling, general, and administrative (SG&A) cost. The research used secondary data and the population of this research was 380 manufacturing companies listed on Indonesia Stock Exchange in the 2016-2020 period. The method used by purposive sampling with 102 manufacturing firms were obtained as the sample of this research. The analytical method used multiple linear regression analysis. The results showed that profitability and size have a positive and significant effect on cost stickiness, asset intensity, free cash flow, and leverage have a negative and significant effect on cost stickiness, and employee intensity has a positive and insignificant effect on cost stickiness.